Pengaruh Implementasi E-Billing Dan E-Filing Terhadap Kepatuhan Wajib Pajak Dengan Taxation Knowledge Sebagai Variabel Moderasi - Roseid, Romana Salsabiila (IJAcc, 2025)
The purpose of this study was to examine the effect of e-Billing and e-Filing implementation on Taxation payer compliance with Taxation Knowledge as a moderating variable at the Kantor Pelayanan Pajak (KPP) Pratama Tangerang Timur. This study uses primary data collected through questionnaires distributed to 115 active Individual Taxation payer (WPOP) respondents registered at KPP Pratama Tangerang Timur. The analysis method used is Moderated Regression Analysis (MRA) with the help of IBM SPSS software version 26. The results showed that; (1) e-Billing implementation has no effect on Taxation payer compliance; (2) e-Filing implementation affects Taxation payer compliance; (3) The implementation of e-Billing and e-Filing together affects taxpayer compliance; (4) Taxation Knowledge cannot moderate the effect of e-Billing implementation on Taxpayer Compliance; (5) Taxation Knowledge can moderate the effect of e-Filing implementation on Taxpayer Compliance. Keywords: e-Billing, e-Filing, Taxationpayer Compliance, Taxation Knowledge